Application of precision medicine: can molecular risk stratification provide new management options for low stage endometrioid ovarian carcinoma?. (1st November 2019) - Krämer, P; Talhouk, A; Bosse, T; Heitz, F; Prader, S; Singh, N; Kommoss, F; Krämer, B; Hartkopf, A; Brucker, S; McAlpine, J; Koebel, M; et al.
Abstract : Introduction/Background: Endometrioid ovarian carcinoma (ENOC) is generally associated with a more favorable prognosis compared to other ovarian carcinoma histotypes. Nonetheless, patients are still treated according to a 'one size fits all' approach. While tumor staging offers some stratification, the development of personalized treatment concepts remain elusive. Our group has recently shown that the Proactive Molecular Risk Classifier for Endometrial Cancer (ProMisE), also provides additional prognostic information in it's ovarian endometrioid counterpart. The aim of this study was to investigate ProMisE in a large cohort of low stage (FIGO I-II) ovarian endometrioid carcinoma. Methodology: After establishment of prognostic groups in >500 ENOC we examined a subset of n=379 FIGO stage I-II cases. Cases were aligned into low risk POLE mutant (POLE); moderate risk mismatch repair deficient (MMRd); high-risk p53 abnormal (p53abn); and a final moderate risk category lacking these biomarkers (p53wt). Kaplan-Meier survival analysis was performed. Results: 4% of cases were POLE, 15% MMRd, 73% p53wt and 8% p53abn. Groups showed distinct progression-free and overall survival (p<0.01). 5-year PFS and OS was 74% in p53abn, 89% in MMRd, 93% in p53wt, and 100% in POLE cases. Conclusion: ProMisE risk classification provides additional prognostic information in a large cohort of low stage ENOC. In the context of low-stage ENOC, and especially younger women wishing to preserve fertility, the introduction of ProMisE-stratified treatment algorithms may serve not only to improve patient care overall but to reduce chemotherapy burden and highlight cases where fertility-sparing surgeries pose little or no risk. Disclosure: Nothing to disclose.